2019
DOI: 10.1155/2019/5031696
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Leptin Receptor and Effects of Leptin on Papillary Thyroid Carcinoma Cells

Abstract: Background. Obesity has been hypothesized to contribute to the aggressiveness of thyroid cancer through the production of abnormal levels of serum adipokines. Leptin receptor (OB-R) expression has also been documented in papillary thyroid cancer (PTC). Aim. In this translational study, we analyzed in vitro the effects of leptin on the growth and migration of thyroid cancer cells (TPC-1 and K1), the molecular mechanisms underlying leptin’s action, and the influence of prolonged leptin exposure on cell response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…In line with our results, more recently, Celano and colleagues reported that leptin slightly increased cell proliferation of K1 cells but only at the dose of 500 ng/ml at 96 h-time point and increased cell motility [ 8 ]. While, consistent with our result, lower doses of leptin (125 ng/ml) does not impair proliferation in K1 cells.…”
Section: Discussionsupporting
confidence: 92%
“…In line with our results, more recently, Celano and colleagues reported that leptin slightly increased cell proliferation of K1 cells but only at the dose of 500 ng/ml at 96 h-time point and increased cell motility [ 8 ]. While, consistent with our result, lower doses of leptin (125 ng/ml) does not impair proliferation in K1 cells.…”
Section: Discussionsupporting
confidence: 92%
“…In 2019, Celano and colleagues conducted a translational study to analyze in vitro the molecular mechanisms by which leptin may affect the growth and migration of PTC cell lines. They demonstrated that leptin slightly increased the aggressive phenotype of PTC cells by stimulating proliferation and migration of both TPC and K1 cells [74]. Similar results were obtained by Nigro et al [75] in both BCPAP and K1 cell lines.…”
Section: Leptinsupporting
confidence: 72%
“…Celano et al also evaluated the effects of leptin exposure on cells in response to lenvatinib, a protein kinase inhibitor. In these experiments, leptin was not able to affect the effect of lenvatinib [74]. The same study also reported that OB-R transcript and proteins were expressed in all PTC tissues examined, with no significant differences between tumors with the BRAF V600E mutation and BRAF wild-type tumors [74].…”
Section: Leptinmentioning
confidence: 50%
“…In the clinical setting of overweight, adipose tissue is expected to secrete leptin protein [27,28]. An endogenous anti-appetite factor, leptin has also been shown to support the growth of certain tumors, including papillary thyroid carcinoma, that express the leptin receptor [4]. There are a variety of other observations that link leptin and thyroid hormone together at cancer cells.…”
Section: Gene Expression In Thyroid Cancer Cells Exposed To Leptinmentioning
confidence: 99%
“…The clinical behavior of thyroid gland cancers is seen to reflect gene mutation and/or epigenetic changes [1,2], and effects of circulating or local trophic factors [3,4]. Circulating trophic factors include target tissue-specific thyrotropin (TSH) secreted by the pituitary gland and adipose tissue-source leptin, which enhances growth of a variety of tumors, including those of the thyroid gland [5].…”
Section: Introductionmentioning
confidence: 99%